Physical and optical characterization of yttrium aluminum monoclinic prepared via citrate-nitrate sol-gel and mechanical alloying method - Mohd Zawawi, Mohd Khairul Ikhwan (2014)
Obtaining single-phase polycrystalline YAM (yttrium aluminum monoclinic, Y4Al2O9) has been a difficult effort since YAG (yttrium aluminum garnet, Y3Al5O12) and YAP (yttrium aluminum perovskite, YAlO3) also invariably present as second phase. YAM, unlike the other two compounds, was extensively studied for its application as scintillators, phosphors and as a laser hosts due to possess of garnet and perovskite structure. The investigation on the YAM itself is considered poor and lacking because very few reports have been published regarding this material even though YAM was discovered along with YAG and YAP. Hence, for the first time sol-gel citrate-nitrate combustion process (SGCNCT) and mechanical alloying (MA) are to be employed in an attempt to achieve the desired pure single phase. The SGCNCT of yttrium and aluminum precursor in a 2/1 ratio directly forms YAM without going through a transition phase. The polycrystalline YAM powders obtained by this process were characterized by DTA/TG, XRD, 27Al NMR, FTIR and UV-VIS spectrometer for the analysis of structural and optical properties. Fully dispersible, unaggregated polycrystalline YAM powders were obtained after heat treatment at 740 oC for 10 h. The formation temperature of the YAM single phase was found to be much lower (700 oC) than that at the conventional solid state reaction which required high temperature around 1917 oC. In the normal sol-gel (SG) process, citric acid forms numerous tiny enclosures that have the constituent cations at the molecular level, leading to a reduction of the diffusion length and the enhancement of the reactivity of the precursors. The reactivity seems to have been further greatly enhanced with the inclusion of the combustion step in the sol-gel process. Hence the SGCNCT process yields pure YAM while the SG process alone has always yielded mixed phase. However, it is difficult to synthesize the YAM phase at lower temperature by the MA process as the reaction between oxides occurs at higher temperature. From the optical analysis, it was confirmed that the YAM behaves as insulator as it has the energy band gap value higher than 3 eV.